Resolving Domestic Violence Issues: The Contribution of KUPI Interpretation in Gender-Responsive Qur’anic Interpretation - Sabila Dwi Jayanti; Muhammad Kudhori (Jurnal test, 2026)
Domestic violence (KDRT) remains a significant issue in Indonesia, with high numbers of reported cases each year. Many of these cases are linked to gender inequality, and misinterpretations of Qur’anic verses often justify patriarchal practices within marriage. This study aims to analyze the interpretations of KUPI (Indonesian Women Ulama Congress) regarding Qur’anic verses related to KDRT and to explore how their progressive interpretations offer solutions to gender inequality in domestic settings. A qualitative, descriptive-analytical approach was used, with data sourced from KUPI’s fatwas, related academic literature, and interviews with gender-responsive scholars involved in KUPI. The study finds that KUPI’s interpretations of verses such as QS. al-Nisa’ [4]: 34 and QS. al-Baqarah [2]: 233 emphasizes equality, respect, and justice, rejecting violence and reinforcing mutual rights within marriage. This research contributes to the development of gender-responsive Qur’anic interpretation and offers new insights into addressing KDRT through Islamic law. For further research, it is recommended that field-based studies be conducted to examine the actual impact of KUPI interpretations on the prevention of domestic violence in Muslim communities, including through interviews with victims, advocates, and female religious scholars who are directly involved.